Interannual variability of precipitation in brazilian semi-arid cities between 1984 and 2015 - Souza, César Lincoln Oliveira de; Nogueira, Virgínia de Fátima Bezerra; Nogueira, Valner da Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Rainfall variations affect the economy of a region directly. The semi-arid region in northeastern Brazil suffers drastic effects of such variability, which harms the agriculture and the availability of water resources. Were analyzed the influence of global climate variability modes in semiarid cities of rainfall in the states of Pernambuco, Paraíba, Ceará and Rio Grande do Norte. The climatology of 70 (seventy) locations throughout the four states and the correlation of the rainy season of these stations with El Niño–Southern Oscillation (ENSO) and the Atlantic Dipole were performed. Most stations showed five months of rainy season, from January to May. The Ceará region was the most affected by the interannual variability patterns. The variability of patterns affected the four studied states in different ways, however, the rainy seasons in the whole region suffered a large influence of the SST anomalies of the South Atlantic Tropical Basin.